2011
DOI: 10.1080/04419057.2011.630787
|View full text |Cite
|
Sign up to set email alerts
|

An examination of not-for-profit volunteer tourism sending organisations' guiding considerations that influence volunteer tourism programmes

Abstract: This exploratory study examines the guiding considerations that not-for-profit volunteer tourism sending organisations utilise in designing and implementing volunteer tourism programs. These considerations encompass overarching factors that affect the strategic and operational direction sending organisations take, influencing their choice of activities and providing the framework for their programs.The study explores the vision and mission statements of not-for-profit sending organisations along with their pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…VT is becoming increasingly popular around the world (Conran, 2011; Keese, 2011) with tourists who want to immerse themselves in local culture, establish deeper relationships with local communities, and contribute to community development and nature conservation (Ong et al, 2011; Ooi & Laing, 2010; Sin, 2009). Defined as using free time and income to travel to help others in need (McGehee & Santos, 2005), it is positioned in the range of alternative tourism.…”
Section: Introductionmentioning
confidence: 99%
“…VT is becoming increasingly popular around the world (Conran, 2011; Keese, 2011) with tourists who want to immerse themselves in local culture, establish deeper relationships with local communities, and contribute to community development and nature conservation (Ong et al, 2011; Ooi & Laing, 2010; Sin, 2009). Defined as using free time and income to travel to help others in need (McGehee & Santos, 2005), it is positioned in the range of alternative tourism.…”
Section: Introductionmentioning
confidence: 99%
“…NGOs use different approaches and strategies, with different outcomes, in developed and developing countries respectively [31, 32, 3647]. Some analysts have argued that NGOs have successfully used ecotourism as a local conservation tool, either by operating tours, influencing the management of protected areas, or raising local awareness [24, 32, 33, 36, 43, 4853]. Other authors, however, have concluded that NGOs may be driven more by global discourses, such as those related to poverty alleviation, development, conservation, equity, and the role of non-state organisations; and that they may prioritize their own agendas over local communities and conservation needs [5457].…”
Section: Introductionmentioning
confidence: 99%
“…Many authors, for example, have suggested that NGOs in developed countries preferentially operate ecotourism enterprises themselves, or form partnerships with government agencies in tourism policy and management for protected areas [24, 4042, 49, 51–53]. In developing countries, in contrast, ecotourism approaches by NGOs commonly combine nature conservation and poverty alleviation, often in challenging political circumstances.…”
Section: Introductionmentioning
confidence: 99%
“…Other literature reveals some general assumptions about roles and responsibilities of volunteer tourism actors that infer a particular understanding of the organization. For instance, the literature frequently argues that volunteer tourism organizations are responsible for meeting the diverse needs of stakeholders including volunteer tourists and host communities (Coghlan & Noakes, 2012;Ong et al, 2011;Raymond, 2008a) and that good practice adopted by volunteer tourism organizations is central to maintaining a sustainable and responsible volunteer tourism industry (Wearing & McGehee, 2013a, 2013b. Such attributions of responsibility suggest that these researchers are, at least implicitly, interpreting volunteer tourism organization in terms of fixed and solid structures although these assumptions are not made explicit.…”
Section: Liquid Organization and Volunteer Tourismmentioning
confidence: 99%